Diastereoselective Synthesis of Glycosyl Phosphates by Using a Phosphorylase–Phosphatase Combination Catalyst. Issue 52 (13th November 2015) - Wildberger, Patricia; Pfeiffer, Martin; Brecker, Lothar; Nidetzky, Bernd
Abstract: Sugar phosphates play an important role in metabolism and signaling, but also as constituents of macromolecular structures. Selective phosphorylation of sugars is chemically difficult, particularly at the anomeric center. We report phosphatase‐catalyzed diastereoselective "anomeric" phosphorylation of various aldose substrates with α‐D ‐glucose 1‐phosphate, derived from phosphorylase‐catalyzed conversion of sucrose and inorganic phosphate, as the phosphoryl donor. Simultaneous and sequential two‐step transformations by the phosphorylase–phosphatase combination catalyst yielded glycosyl phosphates of defined anomeric configuration in yields of up to 70 % based on the phosphate applied to the reaction. An efficient enzyme‐assisted purification of the glycosyl phosphate products from reaction mixtures was established. Abstract : Clever combination : Phosphatase‐catalyzed diastereoselective synthesis of various glycosyl phosphates from unprotected aldose substrates was achieved, with α‐D ‐glucose 1‐phosphate, derived from the phosphorylase‐catalyzed conversion of sucrose and inorganic phosphate, as the phosphoryl donor. Simultaneous and sequential two‐step transformations by the phosphorylase–phosphatase combination catalyst gave α‐D ‐/β‐L ‐aldose 1‐phosphates in up to 70 % yield.